MEMAKNAI PEMENUHAN HAK-HAK PEREMPUAN DALAM IMPLEMENTASI CEDAW TERHADAP PEMBAGIAN WARIS ISLAM - Ananda Luthfiyyah Azwan (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2021)
Abstract: All possibilities will be done by human beings to ensure a decent life, including by gaining proprerties. However, no human beings have the capabilty to avoid death. It is obvious that humans will face their death and leave their properties which shall be distributed to the heirs. Islam acknowledges inheritance rights both for men and women which has been stipulated in inheritance Syaria law. Nonetheless, the disposition of inheritance between men and women are not literally equal, but referring the balanced-equality principle according to the general obligations of men and women. This research paper aims to inform the implementation of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) in fulfilling women’s inheritance rights. Through a qualitative research method, this research proves that women’s inheritance rights has a relationship with feminism. Western feminism demands the same rights between men and women. Somehow, the western feminism hermeneutics is irrelevant with the distribution of property in inheritance Syaria law due to the dicrepancy between the feminism concept and the balanced-equality principle. Syaria law do acknowledged women’s right in inheritance, but, the western feminism concept could not be implemented in Islamic inheritance as it contradicts to Al-Qur’an, Hadits, and Ijma.Keywords: CEDAW; Islamic Inherintance; Feminism; Equality of Rights